Demonstration of Observation of Dislocations in GaN by Novel Birefringence Method. Issue 4 (30th December 2019) - Tanaka, Atsushi; Inotsume, Syo; Harada, Shunta; Hanada, Kenji; Honda, Yoshio; Ujihara, Toru; Amano, Hiroshi
Abstract : Herein, a newly developed birefringence microscope is used to observe dislocations in gallium nitride (GaN) substrates. The comparison results of the observation method using this microscope with other observation methods, such as X‐ray topography and Raman microscopy, confirms that dislocations in a GaN substrate can be detected with a birefringence microscope. In addition, the observation can be carried out as easily as with an optical microscope. It is also found that under certain observation conditions, the direction of the edge component of dislocations can be determined. Abstract : A newly developed birefringence microscope is used to observe dislocations in gallium nitride (GaN) substrates. It is confirmed that dislocations in a GaN substrate can be detected with a birefringence microscope as easily as with an optical microscope. It is also found that under certain observation conditions, the direction of the edge component of dislocations can be determined.